Evaluasi Kepuasan Mahasiswa Prodi Sistem Informasi terhadap Akun @si.amikompwt menggunakan metode EUCS - Mufid Mujahiddin; Abdul Azis (Hemispheres Press, 2022)
The @si.amikompwt account is an Instagram account part of a higher education institution namely Amikom University Purwokerto. The @si.amikompwt account is the official account of one of the Study Programs at Amikom University Purwokerto which focuses on the Information Systems Study Program. The content shared on this account is very diverse, not only about Study Programs, but also other educational content. With the presence of the Information Systems Study Program account, it is hoped that more people will be known and of course be able to inform all things related to lecture activities, especially to students in the Information Systems Study Program. However, based on observations and interviews, the content displayed on the @si.amikompwt account is not very interesting, some students, especially in the Information Systems Study Program, are not happy or satisfied with this account. Therefore, a study is needed to evaluate student satisfaction on the account of this Information Systems Study Program. The appropriate method for evaluating this satisfaction is the EUCS method. The EUCS method is a method that consists of 5 variables, namely content, accuracy, format, ease of use, and timeliness variables. The purpose of this study was to find out whether the variables of the EUCS method had an effect on student satisfaction. The results of this study are the variables of user convenience and timeliness have a significant effect on user satisfaction, while the variables of content, accuracy, and form have no significant effect on the variable of user satisfaction. Keywords : Information Systems Study Program; EUCS; @si.amikompwt account; evaluation.